Case Report: Excision of Left Maxillary Osteosarcoma in a 16-Year-Old Boy Under General Anesthesia with Difficult Airway Procedure - Julia, Listyo Lindawati; Kapuangan, Christopher (Writing Center IMERI FMUI, 2024)
Osteosarcoma is a rare, malignant bone tumor commonly found in adolescents, affecting the long bones. Maxillary involvement, though less frequent, can present significant challenges in surgical resection and anesthetic management. This case describes a 16-year-old male with a maxillary osteosarcoma sinistra undergoing excision under general anesthesia, performed with difficult airway intubation devices. Endotracheal tube (ETT) insertion via nasal intubation is performed with awake intubation. At the end of surgery, the patient was extubated uneventfully and referred to ICU.